Communicative action and supportive behaviors for environmental CSR practices: an attitude-based segmentation approach. (8th April 2020) - Li, Jo-Yun; Overton, Holly; Bhalla, Nandini
Abstract : Purpose: While the segmentation approach has been frequently employed to explore individuals' environment-friendly behaviors, the investigation of environmental corporate social responsibility (CSR) communication by using such a method is limited. Given that the importance of the role of public segmentation is well documented in both public relations and environmental management literatures, the present study attempts to fill the gap by exploring whether consumers can be segmented on the basis of attitudinal factors, and, if so, how this segmentation informs communication efforts aimed at promoting companies' environmental CSR programs. Design/methodology/approach: This segmentation approach is examined based on a survey of 470 participants. Results of a k -means cluster analysis identified three subgroups: active publics, aware publics and latent publics. Findings: Survey results provide empirical support evidence on how different public segmentation approaches can be used to predict individual communication behaviors on environmental CSR issues. Segmentation approach that considered individuals' attitudes on environmental issues and their perceptions on company environmental CSR practices helps identify three subgroups. Significant differences regarding communicative action and supporting behaviors among the three groups are identified and discussed. Originality/value: This study provides key insights about public segmentation and different publics' communicative action, and supportive behaviors provide direction for future research investigations that will strengthen theoretical arguments and best practices in public relations.